Cerámica y luz en el cristianismo de la Antigüedad tardía: A propósito de un nuevo ejemplar de lucerna de asa plástica con crismón - Vizcaíno Sánchez, Jaime (Hispania sacra, 2022)
We analyze a lamp reflector with chrismon recently found at Carthago Spartaria (Cartagena). In this work, an iconographic and functional analysis of this unpublished piece is approached. The chrismon is frequently shown on ARSW bowls or lamps produced between the 4th and the 5th centuries. However, the Tunisian lamp reflectors are very scarce. They are linked to the typological evolution of Early Christian bronze prototypes, in which the reflectors allowed a play of light and shadow with the motif stamped on them. The low impact on the Mediterranean basin allows us to derive data on very little use and perhaps linked to the liturgy of Christian communities.